Open Source Information's Blind Spot: Human and Machine Bias in International Criminal Investigations. (7th April 2021) - McDermott, Yvonne; Koenig, Alexa; Murray, Daragh
Abstract: Digital open source information has been heralded for its democratizing potential, insofar as it allows access to a much broader range of sources and voices than would normally be consulted through traditional methods of information gathering for international criminal investigations. It also helps to overcome some of the physical access barriers that are commonplace in international criminal investigations. At a time when the use of digital open source information is becoming more widespread, this article warns of the cognitive and technical biases that can impact upon two key stages of an investigation: finding relevant information and analysing that information. At the information-gathering stage, there are particular crimes, regions and groups of people whose experiences are more likely to be overlooked or hidden in digital open source investigations. When it comes to analysing digital open source information, there is a danger that cognitive and technical biases may influence which information is deemed most relevant and useful to an international criminal investigation, and how that information is interpreted. This article proposes some steps that can be taken to mitigate these risks.